Hierarchical Distribution Models of the Invasive Fish Carassius gibelio and Pseudorasbora parva and Prediction of Their Impact on Lake Sevan (Journal of Innovative Solutions for Eco-Environmental Sustainability, 2025)
The hypothesis of climatic niche conservatism (CNC) of invasive fish species, Prussian carp Carassius gibelio (Bloch, 1782) and Stone moroko Pseudorasbora parva (Temminck & Schlegel, 1846), was tested, and their hierarchical spatial distribution models (hSDM) were constructed in Armenia and adjacent territories using a global set of species occurrence records (SORs) together with climatic, topographic, and dispersal-related variables. Results show that the CNC hypothesis is not rejected for either species. The climatic niches of C. gibelio and P. parva differ considerably (similarity index ~27%), with the niche breadth of C. gibelio significantly wider than that of P. parva (P
Keywords: invasions; freshwater; Prussian carp; Stone moroko; niche conservatism; SDM